Spectroscopy of doped lithium niobate - Amin, Jaymin (2000)
The values of measured and calculated spectroscopic quantities oflithium niobate doped with rare earth and transition metal ions, such as polarized emission and absorption cross sections, variation of fluorescence life time with temperature and concentration of the dopant, Judd-Ofelt coefficients, non-radiative transition probabilities and energy levels are presented. Wherever published data is available, comparison with measured or calculated data presented in this work is carried out. The theories utilized in the interpretation of the experimental results, such as Judd-Ofelt theory, Fuchtbauer-Lademburg relation and McCumber theory are summarily presented.